2005
DOI: 10.1017/s1743921305003637
|View full text |Cite
|
Sign up to set email alerts
|

The chemical evolution of subpopulations in the Carina dwarf spheroidal

Abstract: Abstract. We present the observed metallicity distribution for 437 red giants in the Carina dwarf spheroidal (dSph) galaxy that was derived from FLAMES medium-resolution spectroscopy of the near-infrared Ca triplet (CaT). We find a mean [Fe/H] of −1.7 dex and a full spread in metallicities of at least one dex. Most of this width is due to the occurrence of three populations at different [Fe/H], which are likely to be related to the three star forming (SF) episodes that governed Carina's evolution and also corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…On the other hand, Koch et al (2005) found that for the Carina dSph, there is a larger age spread (from 2 Gyr to more than 11 Gyr), while its colour-magnitude diagram shows a narrow RGB distribution. The large age spread implies that Carina dSph must have undergone various episodes of star formation process.…”
Section: Metallicity Distributionsmentioning
confidence: 94%
“…On the other hand, Koch et al (2005) found that for the Carina dSph, there is a larger age spread (from 2 Gyr to more than 11 Gyr), while its colour-magnitude diagram shows a narrow RGB distribution. The large age spread implies that Carina dSph must have undergone various episodes of star formation process.…”
Section: Metallicity Distributionsmentioning
confidence: 94%
“…2). In any case, Koch et al (2007) make it clear from their analysis of Leo II that there is compelling evidence for velocity anisotropy in dwarfs.…”
Section: Modelling the Los Velocity Dispersionsmentioning
confidence: 99%
“…Note that although there are two parameters for the anisotropy, the profile required is virtually the same for 6/8 dwarfs (see fig 2). In any case, Koch et al (2007) make it clear from their analysis of Leo II that there is compelling evidence for velocity anisotropy in dwarfs.…”
Section: Modeling the Los Velocity Dispersionsmentioning
confidence: 99%
“…The last few years have seen a substantial increase in kinematic data for dSphs, largely thanks to large optical telescopes such as ESO's Very Large Telescope (VLT), Keck, Gemini, and Magellan. Programs such as our VLT Large Programme Wilkinson et al 2006;Koch et al 2006b) concentrated on obtaining radial velocity dispersion profiles for as many stars as possible out to the optical boundaries of the target dSphs. Results of our program are also described in the contribution by Wyse & Gilmore in these proceedings.…”
Section: Radial Velocity Measurements Across the Full Angular Extent ...mentioning
confidence: 99%